Tips in the management of burns - Shalabh Kumar (Wolters Kluwer Medknow Publications, 2020)
Burns is a serious health problem in our country. Burn management is a complex and resource intensive process and requires a dedicated multidisciplinary team working in coordination in all the aspects of burn care simultaneously. Most burn patients get treated by the general practitioner primarily and then referred to higher centers. Specialized burn centers are few in number, and affordable care is hard to find other than government run institutions. A lot of research has been done in the fields of burn resuscitation, nutrition, synthetic and biologic dressings, and surgical management of burn wounds, etc., and several advances have been made, but most institutes managing burns are restricted by their availability of resources and high patient load and hence adopt their own protocols based on their patient characteristics, resources, and experience in treating burns. Here, I have shared a few tips and wisdom I have gained in the management of burns based on my experience of almost 30 years in treating burns at a government run tertiary burn care center. Despite all efforts, severe burns are still associated with very high morbidity and mortality and so a concerted effort needs to be made at the national as well as grass root level to raise the awareness and education regarding burns safety and prevention of burns.